Large-vessel involvement is predictive of multiple relapses in giant cell arteritis. (May 2021) - de Mornac, Donatienne; Espitia, Olivier; Néel, Antoine; Connault, Jérôme; Masseau, Agathe; Espitia-Thibault, Alexandra; Artifoni, Mathieu; Achille, Aurélie; Wahbi, Anaïs; Lacou, Mathieu; Durant, Cécile; Pottier, Pierre; et al.
Background: Giant cell arteritis (GCA) is the most common systemic vasculitis. Relapses are frequent. The aim of this study was to identify relapse risk factors in patients with GCA with complete large-vessel imaging at diagnosis. Methods: Patients with GCA followed in our institution between April 1998 and April 2018 were included retrospectively. We included only patients who had undergone large vascular imaging investigations at diagnosis by computed tomography (CT)-scan and/or positron emission tomography (PET)-scan and/or angio-magnetic resonance imaging (MRI). Clinical, biological, and radiological data were collected. Relapse was defined as the reappearance of GCA symptoms, with concomitant increase in inflammatory markers, requiring treatment adjustment. Relapsing patients (R) and non-relapsing patients (NR) were compared. Relapse and multiple relapses (>2) risk factors were identified in multivariable Cox analyses. Results: This study included 254 patients (73.2% women), with a median age of 72 years at diagnosis and a median follow up of 32.5 months. At diagnosis, 160 patients (63%) had an inflammatory large-vessel involvement on imaging, 46.1% (117 patients) relapsed at least once, and 21.3% (54 patients) had multiple relapses. The median delay of first relapse after diagnosis was 9 months. The second relapse delay was 21.5 months. NR patients had more stroke at diagnosis than R ( p = 0.03) and the brachiocephalic trunk was involved more frequently on CT-scan ( p = 0.046), as carotids ( p = 0.02) in R patients. Multivariate Cox model identified male gender [hazard ratio (HR): 0.51, confidence interval (CI) (0.27–0.96), p = 0.04] as a relapse protective factor, and peripheral musculoskeletal manifestations [HR: 1.74 (1.03–2.94), p = 0.004] as a relapse risk factor. Peripheral musculoskeletal manifestations [HR: 2.78 (1.23–6.28), p = 0.014], negative temporal artery biopsy [HR: 2.29 (1.18–4.45), p = 0.015], large-vessel involvement like upper limb ischemia [HR: 8.84 (2.48–31.56), p = 0.001] and inflammation of arm arteries on CT-scan [HR: 2.39 (1.02–5.58), p = 0.04] at diagnosis were risk factors of multiple relapses. Conclusion: Male gender was a protective factor for GCA relapse and peripheral musculoskeletal manifestations appeared as a relapsing risk factor. Moreover, this study identified a particular clinical phenotype of multi-relapsing patients with GCA, characterized by peripheral musculoskeletal manifestations, negative temporal artery biopsy, and large-vessel involvement with upper limb ischemia or inflammation of arm arteries. Plain language Summary: At giant cell arteritis diagnosis, large-vessel inflammatory involvement is predictive of multiple relapses 46.1% of patients with GCA relapse, and 21.3% undergo multiple relapses; Male gender appears as a protective factor for relapsing in GCA; Peripheral musculoskeletal manifestations are a relapse and multiple relapses risk factor; A negative temporal artery biopsy is predictive of multiple relapses; Large-vessel involvement is predictive of multiple relapses.